Analisis Keuntungan Usaha Ternak Ayam Kampung (Gallus gallus domesticus) Di Desa Madurejo Kecamatan Sambung Makmur Kabupaten Banjar Provinsi Kalimantan Selatan - Zuraida; Wasdiyanta (Fakultas Pertanian UVAYA Banjarmasin, 2023)
This research is motivated by unstable feed prices and yields which will affect the welfare of farmers. The aim of this research is technically to determine free-range chicken cultivation and financially to determine costs, revenues and profits, with a sampling method using the Census Method. The results of the research are the total cost of Rp. 995,143, total receipt Rp. 2,090,000 and the profit amount is Rp. 1,094,857 production levels obtained were 209 head or an average of 20.9 head/respondent, at a price of Rp. 100,000/head